Turning On Lights to Stop Neurodegeneration: The Potential of Near Infrared Light Therapy in Alzheimer's and Parkinson's Disease - Johnstone, Daniel M.; Moro, Cécile; Stone, Jonathan; Benabid, Alim-Louis; Mitrofanis, John (Frontiers in Neuroscience, 2016)
Alzheimer’s and Parkinson’s disease are the two most common neurodegenerative disorders. They develop after a progressive death of many neurones in the brain. Although therapies are available to treat the signs and symptoms of both diseases, the progression of neuronal death remains relentless, and it has proved difficult to slow or stop. Hence, there is a need to develop neuroprotective or disease-modifying treatments that stabilise this degeneration. Red to infrared light therapy (λ=600-1070nm), and in particular light in the near infrared (NIr) range, is emerging as a safe and effective therapy that is capable of arresting neuronal death. Previous studies have used NIr to treat tissue stressed by hypoxia, toxic insult, genetic mutation and mitochondrial dysfunction with much success. Here we propose NIr therapy as a neuroprotective or disease-modifying treatment for Alzheimer’s and Parkinson’s patients.